ФОРМИРОВАНИЕ НАНОЧАСТИЦ В ВОДНОЙ СРЕДЕ ИЗ МИШЕНИ СИЛУМИНА - Маркевич, М.И.; Асанов, Д.Ж.; Камалов, А.Б. (SCIENCE and SOCIETY, 2023)
Laser ablation opens up wide opportunities for obtaining such materials, since the resulting particles are of high purity. In this work, an Al…%Si alloy (silumin) was used as the target, and distilled water was used as the medium in which the target was located. For processing silumin, an yttrium aluminum garnet laser (LS-2134D) was used. with a wavelength of 1064 nm, generating in a two-pulse mode. The decomposition of silumin was obtained in water into individual nanoparticles of aluminum and silicon (energy input 1500 J, exposure time 25 min.). Some aluminum particles are faceted, which allows us to talk about their crystallinity